2017
DOI: 10.1088/1752-7163/aa857d
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of breath tests for pneumoconiosis using an electronic nose

Abstract: Breath analyses have attracted substantial attention as screens for occupational environmental lung disease. The objective of this study was to develop breath tests for pneumoconiosis by analysing volatile organic compounds using an electronic nose. A case-control study was designed. We screened 102 subjects from a cohort of stone workers. After excluding three subjects with poorly controlled diabetes mellitus and one subject with asthma, 98 subjects were enrolled, including 34 subjects with pneumoconiosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…A few other studies compared individual ILDs with healthy controls and COPD patients [ 58 61 ]. Breathprints of patients with idiopathic pulmonary fibrosis (IPF), ILD associated with connective tissue disease and pneumoconiosis were significantly different from healthy controls [ 59 61 ]. In sarcoidosis patients, the breathprint of patients with untreated sarcoidosis differed from healthy controls, implying that eNose technology may be used for initial diagnosis.…”
Section: Current Clinical Applicationmentioning
confidence: 99%
“…A few other studies compared individual ILDs with healthy controls and COPD patients [ 58 61 ]. Breathprints of patients with idiopathic pulmonary fibrosis (IPF), ILD associated with connective tissue disease and pneumoconiosis were significantly different from healthy controls [ 59 61 ]. In sarcoidosis patients, the breathprint of patients with untreated sarcoidosis differed from healthy controls, implying that eNose technology may be used for initial diagnosis.…”
Section: Current Clinical Applicationmentioning
confidence: 99%
“…A standard breath test must control the flow rate and humidity and collect alveolar air that contains the metabolites from the alveolar-capillary membrane and released into the alveolar space [ 52 ]. To improve the efficiency of the electronic nose breath test, we suggest that future research can continue to optimize the breath collection device, which can automatically control the flow rate and humidity and monitor the CO 2 concentration to collect alveolar air containing volatile biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of early-stage pneumoconiosis is difficult in clinical practice using conventional methods [221]. Yang et al [206] analyzed the exhaled breath VOCs of 34 subjects with pneumoconiosis and 64 healthy patients using a C320 e-nose. Performance of the e-nose using a prediction model based on linear discriminant analysis (LDA) indicated that C320-discriminations of sample types had high specificity (88.0%), acceptable sensitivity (67.9%), and good accuracy (80.8%) in the training set.…”
Section: Human Disease Detectionmentioning
confidence: 99%